The Influence of Business Ethics, Work Ethic, Employee Engagement Remuneration on the Company's Reputation in Public Plantation Companies - Sanjaya, Juna; Nurhayati, Nurhayati (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to investigate the relationship between business ethics, work ethic, remuneration, and corporate reputation in public plantation companies. This study used quantitative approaches by selecting 100 employees from open plantation enterprises through random sampling. A method called Partial Least Squares (PLS) is employed for the data analysis. The results of the analysis show a significant relationship between business ethics, work ethic, remuneration with company reputation. It was found that strong business ethical practices, a positive work ethic, and fair remuneration can contribute positively to a company's reputation. These findings indicate the importance of implementing these practices in improving the company's image in the eyes of the public. This research provides valuable insights for the management of publicly traded plantation companies in understanding the factors that affect their company reputation. Practical implications of these findings include an emphasis on improving a culture of business ethics, strengthening work ethics, and implementing fair and competitive remuneration policies. This is expected to help companies strengthen their position in the market and gain greater support from various stakeholders.